Development of Online Inquiry Mathematics Learning Model Based on Javanese Culture Ethnomathematics - Pardimin Pardimin; Dafid Slamet Setiana; Didi Supriadi (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2021)
This study aims to develop an online inquiry mathematics learning model based on Javanese Cultural Ethnomathematics. To achieve this goal, development research is carried out which refers to the educational development model from Plomp with the following stages: Initial Investigation Stage, Design/Design Stage, Realization/Construction Stage, Test Stage, Evaluation, and Revision, and Dissemination and Implementation Stage. In this study, the initial investigation stage and design stage were carried out. The initial investigation phase includes field observations, literature studies and FGD (Focus Group Discussion). The design phase is carried out by designing learning model books along with learning tools and validation is carried out. Data collection techniques used are interviews, observations, and questionnaires. The data and information that have been collected are then analyzed using qualitative descriptive analysis techniques. The results showed that the development stage of the learning model had reached the design stage. The results of the research achieved were after carrying out observations at school and field observations at ten Javanese Cultural sites, then FGD was carried out to obtain the syntax of an ethnomathematics-based online inquiry learning model. The syntax of the online inquiry learning model based on Javanese Culture ethnomathematics is: Orientation; Formulating the problems; Formulating the hypothesis; Collecting data; Test the hypothesis; Formulating conclusions; and Communicating results. The syntax of the learning model that has been set is used as a guide in developing an online inquiry-based mathematics learning model book based on Javanese Culture ethnomathematics. The results of the validity test showed that the learning model book was declared valid and feasible to use.